Therapeutic effect of palmitoylethanolamide in cognitive decline: A systematic review and preliminary meta-analysis of preclinical and clinical evidence - Colizzi, Marco; Bortoletto, Riccardo; Colli, Chiara; Bonomo, Enrico; Pagliaro, Daniele; Maso, Elisa; Di Gennaro, Gianfranco; Balestrieri, Matteo (Frontiers in Psychiatry, 2022)
Cognitive decline is believed to be associated with neurodegenerative processes involving excitotoxicity, oxidative damage, inflammation, and microvascular and blood-brain barrier dysfunction. Interestingly, research evidence suggests upregulated synthesis of lipid signaling molecules as an endogenous attempt to contrast such neurodegeneration-related pathophysiological mechanisms, restore homeostatic balance, and prevent further damage. Among these naturally occurring molecules, palmitoylethanolamide (PEA) has been independently associated with neuroprotective and anti‐inflammatory properties, raising interest into the possibility that its supplementation might represent a novel therapeutic approach in supporting the body-own regulation of many pathophysiological processes potentially contributing to neurocognitive disorders. Here, we systematically reviewed all human and animal studies examining PEA and its biobehavioral correlates in neurocognitive disorders, finding 33 eligible outputs. Studies conducted in animal models of neurodegeneration indicate that PEA improves neurobehavioral functions, including memory and learning, by reducing oxidative stress and pro-inflammatory and astrocyte marker expression as well as rebalancing glutamatergic transmission. PEA was found to promote neurogenesis, especially in the hippocampus, neuronal viability and survival, and microtubule-associated protein 2 and brain-derived neurotrophic factor expression, while inhibiting mast cell infiltration/degranulation and astrocyte activation. It also demonstrated to mitigate β-amyloid-induced astrogliosis, by modulating lipid peroxidation, protein nytrosylation, inducible nitric oxide synthase induction, reactive oxygen species production, caspase3 activation, amyloidogenesis, and tau protein hyperphosphorylation. Such effects were related to PEA ability to indirectly activate cannabinoid receptors and modulate proliferator‐activated receptor‐α (PPAR‐α) activity. Importantly, preclinical evidence suggests that PEA may act as a disease-modifying-drug in the early stage of a neurocognitive disorder, while its protective effect in the frank disorder may be less relevant. Limited human research suggests that PEA supplementation reduces fatigue and cognitive impairment, the latter being also meta-analytically confirmed in 3 eligible studies. PEA improved global executive function, working memory, language deficits, daily living activities, possibly by modulating cortical oscillatory activity and GABAergic transmission. There is currently no established cure for neurocognitive disorders but only treatments to temporarily reduce symptom severity. In the search for compounds able to protect against the pathophysiological mechanisms leading to neurocognitive disorders, PEA may represent a valid therapeutic option to prevent neurodegeneration and support endogenous repair processes against disease progression.